PENGARUH SHOPPING LIFESTYLE, FASHION INVOLVEMENT DAN HEDONIC SHOPPING VALUE TERHADAP IMPULSE BUYING PEMBELIAN HIJAB MEREK RABBANI DI KECAMATAN SAWOO KABUPATEN PONOROGO PADA MASA PANDEMI - Desty, Iga Dwi; Wijayanto, Heri; Purwaningrum, Titis (Bussman Journal : Indonesian Journal of Business and Management, 2022)
Hedonic Shopping Value on Impulse Buying on Rabbani Brand Hijab Purchases. All data used in the analysis is data obtained from observations, interviews and various literatures concerning Shopping Lifestyle, Fashion Involvement, and Hedonic Shopping Value on Impulse Buying in Rabbani Brand Hijab Purchases in Sawoo District, Ponorogo Regency during the Pandemic Period. Based on research that Shopping Lifestyle has an effect on impulse buying for the purchase of Rabbani brand hijab in Sawoo sub-district during the pandemic, this is evidenced by t count > t table (3.961> 1.985), Fashion Involvement has an effect on impulse buying for Rabbani brand hijab purchases in Sawoo sub-district during the pandemic, this is evidenced by t count > t table (2,499 > 1,985), Hedonic Shopping Value has an effect on impulse buying for the purchase of the Rabbani brand hijab in Sawoo sub-district during the pandemic, this is evidenced by t count > t table (2,130 > 1,985). Simultaneously there is a significant influence between Shopping Lifestyle, Fashion Involvement, and Hedonic Shopping Value on Impulse Buying on Rabbani Brand Hijab Purchases in Sawoo District, Ponorogo Regency during the Pandemic Period, which can be proven by F count > F table (34.3949 > 2.70 ). And the magnitude of the influence of Shopping Lifestyle, Fashion Involvement, and Hedonic Shopping Value on Impulse Buying on the Purchase of Rabbani Brand Hijab in Sawoo District, Ponorogo Regency during the Pandemic Period is 51.8%. While the remaining 48.2% is influenced by other variables that are not in this study.